Effect of cased charges on plain steel and steel-concrete sandwich targets - Rana, M. M. (2021)
When designing light weight protective structures it is important to consider the threat from cased charges. In this research, a steel panel constructed using standard steelwork sections and a steel-concrete sandwich panel were loaded using a cased pipe charge containing 15 kg of TNT equivalent explosive. Central deflections and damage images were collected and were employed to validate finite element (FE) simulations. These were used to compare models using different stand-offs and two simplified smeared loading methods. The results showed that the influence of the localised damage was limited for the loading range considered.